Combination of Nonlinear and Linear Optimization of Transient Gas Networks - Domschke, Pia; Geißler, Björn; Kolb, Oliver; Lang, Jens; Martin, Alexander; Morsi, Antonio (Informs Journal on Computing, 2011)
In this paper, we study the problem of technical transient gas network optimization, which can be considered a minimum cost flow problem with a nonlinear objective function and additional nonlinear constraints on the network arcs. Applying an implicit box scheme to the isothermal Euler equation, we derive a mixed-integer nonlinear program. This is solved by means of a combination of (i) a novel mixed-integer linear programming approach based on piecewise linearization and (ii) a classical sequential quadratic program applied for given combinatorial constraints. Numerical experiments show that better approximations to the optimal control problem can be obtained by using solutions of the sequential quadratic programming algorithm to improve the mixed-integer linear program. Moreover, iteratively applying these two techniques improves the results even further.
Keywords: gas networks; optimal control; mixed-integer programming; nonlinear programming; sequential quadratic programming